A study of periodic and quasi-periodicorientational motion of microrods in a shear flow using optical tweezers - Laas, Alexander (My University, 2014)
The orientational motions of single isolated inertialess microrods are studied in a reversible creeping shear ow. In previous work [12, 24, 30] it was observed that rodlike particles could experience both periodic and quasi-periodic behavior. This work studies how the orientational motion, including periodic and quasi-periodic motion, depends upon the orientational initial conditions, for a single microrod. For the purpose of changing the initial conditions, optical tweezers are installed in the experimental setup. In order to demonstrate that the microdrods and uid are inertialess the ow is reversed and the trajectories before and after the reversal are analyzed. If both the microrod and the ow are inertialess, the orientational motion of the rod is expected to retrace itself when the ow is reversed. The experimental results show that if the ow is reversed smoothly, particles can show this retraceibility. The experimental results also demonstrate that a single rod may exhibit either periodic or quasi-periodic motion, depending solely on its orientational initial condition. The observable dynamics show good agreement with Je ery's equations of motion for an inertialess ellipsoid in a creeping shear flow.
Keywords: Grundläggande vetenskaper; Energi; Annan teknik; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Basic Sciences; Energy; Other Engineering and Technologies; Sustainable Development; Innovation & Entrepreneurship